COMPREHENSIVE ANALYSIS ON COTINUS COGGYGRIA SCOP. LEAVES: PHYTOCHEMICAL CHARACTERIZATION, BIOLOGICAL PROFILE AND DOCKING STUDIES - Seker Karatoprak, Gokce; Kilic, Gokcen; Celik, Ismail; Ilgun, Selen; Kongul Safak, Esra; Kosar, Muberra (Univ Babes-Bolyai, 2023)
The present work aims to evaluate the antioxidant, cytotoxic, enzyme inhibitory, and anti-inflammatory properties of Cotinus coggygria Scop. The leaf extract was analyzed using LC-MS/MS and antioxidant activity was also investigated via several in vitro models (DPPH center dot, ABTS(center dot+), FRAP, metal chelating, inhibition of beta-carotene bleaching, and lipid peroxidation). Enzyme inhibition activity was evaluated on alpha-amylase and alpha-glucosidase. Molecular docking studies were performed to assess the binding efficiency of the identified compounds with alpha-glucosidase. The toxicity of the extract was studied using two breast cancer cell lines as well as healthy fibroblast cell lines (L929). Using LPS induced macrophage cell line model, the anti-inflammatory activity was examined by determining NO, IL-1 beta, IL-6, IL-10, and TNF-alpha levels. The methanol extract significantly affected the alpha-glucosidase enzyme, which also exhibited antioxidant activity. Galloyl hexose and methyl trigallate were found to have the highest binding contact energies for the alpha-glucosidase enzyme, according to docking analyses. Even at a 31.25 mu g/mL concentration, the extract caused 43.46% inhibition in MDA-MB 231, and 48.09% in MCF-7 cell lines. Significant effects on TNF-alpha and IL-6 cytokine levels also proved anti-inflammatory activity. These findings suggest that C. coggygria may serve as an efficient alpha-glucosidase inhibitor and anti-inflammatory agent.
Keywords: Cotinus coggygria; enzyme inhibition; docking; anti-inflammatory; antioxidant; cytotoxicity